The relationship of compound playing skills in football to the selection of the school team - Hussein Ali Hasan Al-Taie,; Ayyd Ali Adhab Al-Saedi,; Ali Shakir Obaid Al-Sultani, (Eximia, 2024)
The research aims to identify the relationship of compound skills to football and selecting players, as the descriptive approach was used to suit the nature of the research problem, which is choosing the best students to perform the compound skills on which football matches often depend. The research sample amounted to (15) students, and in order to implement the research steps, the assistant work team, under the supervision of the researchers, conducted tests for the research sample and then transcribed, analyzed and discussed the results, as it became clear that the compound tests studied have a major role in determining the player’s skill and classifying him among the elite to represent the school team or not.